Forensic social workers’ experiences regarding the non-disclosure of sexual abuse during forensic assessments with black male child victims in South Africa - Rapholo, Selelo Frank (Penerbit Universiti Kebangsaan Malaysia, 2021)
Several studies describe reasons why children are reluctant to disclose sexual abuse. However, there is an incompleteness in understanding how black male child victims do not easily disclose their sexual abuse experiences. This study aimed to describe the experiences of forensic social workers regarding the non-disclosure of sexual abuse during forensic assessments with black male child victims. The ecosystems theory was used to zoom into systems that black male children in South Africa find themselves in which prevent them from disclosing their sexual abuse experiences. A qualitative approach with a descriptive design using a stratified random, purposive and convenient sampling techniques were employed to select fourteen forensic social workers who participated in this study. Semi-structured individual interviews with open ended questions were used to collect data which was analyzed thematically through the help of NVivo 12 Pro software. Findings revealed fear of the consequences to self and patriarchal values as having an influence for the non-disclosure of child sexual abuse amongst black male child victims during forensic assessments. Socio-cultural systems which black male child victims find themselves in were also found to have a very strong influence in their reluctance to disclose sexual abuse. It is therefore imperative that forensic social workers and other experts consider strategies useful to promote the disclosure of child sexual abuse which should focus on reducing fear of consequences of disclosing and rethinking cultural values.